Transcriptome analysis revealed association of some P450 genes with obesity in a polygenic obese mouse model - Simončič, Matjaž (Acta chimica slovenica, 2008)
Superfamily of cytochromoes P450 (CYP) have been extensively investigated in xenobiotic metabolism studies but only a handful of these genes (e.g., Cyp19al and Cpy7al) have been associated with obesity. Examining these associations in animal models is relevant since obesity and metabolic syndrome in humans have become a prevalent health problem. In previous studies we identified four loci affecting obesity in mouse lines selected for high (Fat line) or low (Lean line) body fat content. Here we developed a Congenic line carrying a chromosome 15 obesity segment from the Lean line and compared its liver transcriptome and obesity traits with the original Fat line. Congenic segment exibited therapeutic effect on several obesity-related parameters such as lowering fat depot size by up to 29% and lowering fasting glucose levels. Using the Steroltalk microrray focused on cytochromes P450 and cholesterol metabolism, we identified 9 differentially expressed genes including two Cyp genes (Cyp 26al, Cyp2a4). Given the scacity of literature reporting associations between obesity and Cyps, our results auggest that these genes might play a more pronounced role in regulating obesity than previously thought. Further functional studies are needed to explain the mechanism by which pertubations in these Cyps affect obesity in our polygenic model.
Keywords: citokrom P-450; debelost; holesterol; molekularna genetika; presnova